Maqāmāt as a Path to Purify the Soul: Repentance (Taubat), Wara', Zuhud, Patience, and Tawakkal - Luthfi Ulfia Hasanah (Yayasan Zia Salsabila, 2026)
This study employs a qualitative approach using a library research method by examining classical and contemporary Sufi literature. The data are analyzed descriptively and analytically to understand the meaning, position, and role of each maqām in shaping a Muslim’s spirituality. The findings indicate that each maqām serves an interconnected function and cannot be separated from one another. Repentance forms the foundational stage of soul purification; waraʿ acts as a safeguard for the purity of the heart; zuhd frees the soul from worldly attachments; patience strengthens inner resilience in obedience and trials; while tawakkul cultivates inner peace through complete surrender to Allah SWT. This article affirms that maqāmāt are not exclusively relevant to Sufis but can be applied by all Muslims in their daily lives. Amid the challenges of modern life characterized by materialism and spiritual anxiety, the concept of maqāmāt offers a systematic spiritual framework for forming a Muslim personality that is morally upright, balanced, and oriented toward the values of the Hereafter.